Qualidade de vida de enfermeiros em instituições hospitalares: o público e o privado - Cavalcante, Maria Beatriz de Paula Tavares (2011)
The theme recurs quality of life studies in nursing, especially when dealing with teh Quality of Working Life. However, many times these investigations suggest that only the work of nursing is stressful. Without further deepening the aspects that characterize it. The aim of this study is to apprehend the social representations of nurses about the quality of life in public and private hospitals, and specific objectives describe the sociodemographic variables of nurses in public and private hospitals, and compare the quality of life for public hospital nurses and private sectors. Exploratory, descriptive study mixed and held in two hospitals, one public and one private, with a sample of 40 nurses, who used to support research and the WHOQOL-Bref instrument and the Free Words Association Test as a technique. The data were compiled in SPSS an EVOC-2000, respectively. The Social Representation Theory is configured here as a subsidy that allows cross-checking between the instrumental and the technique adopted in the research. The results indicate the predominance of women in the category, the difference in the profile of age according to the institution, featuring a private institution with the profile younger, the public hospital has a greater number of nurses with a high level of training as well as one in which nurses have better assessment to the current health. For overall health assessment, both groups showed a good evaluation for the quality of life and satisfaction with health. For domains, there was no statistical significance associated with the group. The Free Word Association revealed for both stimuli adopted, health and Leisure were evoked in the central core, with greater representation in the survey. The social representation of nurses on the on the quality of life in public and private hospitals was that they are satisfied with their quality of Life, however, that this satisfactions was hampered by limitations such as health, leisure and general satisfactions of these.